ANDROID-BASED LEARNING MEDIA DEVELOPMENT FOR CHEMICAL BALANCE MATERIALS - Ramlan Silaban; Freddy TM Pannggabean; Melhyada Veronika Panggabean; Pelita Ananda Sianturi; Irving Josafat Alexander (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2021)
This study aims to obtain an innovative android-based chemistry learning media for Chemical Equilibrium material in Class XII MIA. To achieve this goal, research on the type of development using the 4D method has been carried out. The media obtained were tested for feasibility, referring to the feasibility indicators of learning media in the National Education Standards Agency, BSNP involving expert validators. The research result show that(1) An android-based chemistry learning media (ChemsDroid) has been obtained on chemical equilibrium topic.(2). The ChemsDroid media obtained has met the eligibility criteria based on the National Education Standards Agency (BSNP), namely content feasibility, graphic feasibility, language feasibility and presentation feasibility.(3) The results of the perception test showed that students gave a very good response.